Synthesis of Highly Effective alpha-Fe(2)O(3)Catalyst for the Spin Conversion of Liquid Hydrogen - Das, Taraknath; Choi, Jeong-Gil; Oh, In-Hwan (NATL ACAD SCIENCES INDIA, 2020)
A series of alpha-Fe(2)O(3)catalysts were prepared by precipitation method by changing calcination temperatures, solvents, precursor concentration, and bases. The structure and morphology of the synthesized catalysts were characterized by SEM, XRD, XPS, and Raman spectroscopy, and the liquid-phase spin conversion of ortho-hydrogen to para-hydrogen was performed by in situ FTIR spectroscopy at cryogenic temperature 17 K. The spin conversion was affected by catalysts calcination temperature, initial precursor concentration, solvents used, and precipitating agent. The highly dispersed and most active alpha-Fe(2)O(3)was obtained using double-distilled water as solvent and sodium hydroxide solution as precipitating agent followed by calcination at 393 K for 12 h. The formation of hydrated Fe (OH)(3)or FeOOH during synthesis of alpha-Fe(2)O(3)at 393 K dramatically enhanced the catalytic activity and ortho to para-hydrogen spin conversion.